Poly(N-vinylpyrrolidone)-polypeptide based antitumor nanocarrier and cell viable ʟ-arginine, ʟ-aspartic acid and glycine terpolymer - Mbizana, Siyasanga (Stellenbosch : Stellenbosch University, 2018, 2018)
Thesis (PhD)--Stellenbosch University, 2018